2013
DOI: 10.1038/clpt.2013.108
|View full text |Cite
|
Sign up to set email alerts
|

Interchangeability of Gabapentin Generic Formulations in the Netherlands: A Comparative Bioavailability Study

Abstract: To investigate the so-called "drift" with generic-generic drug substitution, a single-dose, four-way crossover comparative bioavailability study was performed involving 24 healthy subjects and three generic and one branded formulation of a tablet containing 800 mg gabapentin as test medication. The results showed that the 90% confidence intervals (CIs) for the area under the drug concentration-time curve (AUC(0-t)) and for the peak drug concentration (C(max)) were within the acceptance range of 80-125% for all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
33
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 25 publications
6
33
0
3
Order By: Relevance
“…The test preparation of gabapentin evaluated in this study was of a different formulation and manufacturer than those evaluated in previous similar publications of gabapentin bioequivalence 21–24. Moreover, our study evaluated the bioavailability of a lower dose of gabapentin preparation (300 mg capsule) than those in former similar studies (400 mg to 800 mg capsules) 2224…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The test preparation of gabapentin evaluated in this study was of a different formulation and manufacturer than those evaluated in previous similar publications of gabapentin bioequivalence 21–24. Moreover, our study evaluated the bioavailability of a lower dose of gabapentin preparation (300 mg capsule) than those in former similar studies (400 mg to 800 mg capsules) 2224…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, our study evaluated the bioavailability of a lower dose of gabapentin preparation (300 mg capsule) than those in former similar studies (400 mg to 800 mg capsules) 2224…”
Section: Discussionmentioning
confidence: 99%
“…6 Whereas the findings are reassuring, prudence dictates that changing the brand of a prescription (whether original or generic) is justified only if there is a good reason for it. This is because medications contain a number of excipients; since these excipients will certainly vary from generic to generic, the safety profile of a generic may change as a function of the contained excipients.…”
Section: Parting Notesmentioning
confidence: 99%
“…Methods: Data was gathered in a 4-way crossover study in 24 subjects with 4 different oral formulations of gabapentin previously concluded to be bioequivalent by non-compartmental analysis. 1 The non-parametric pharmacokinetic modelling software Pmetrics was used, which is capable of identifying unprespecified subpopulations in pharmacokinetic data. 2 Models were validated using visual predictive checks (VPCs) and the Akaike information criterion (AIC).…”
Section: Discussionmentioning
confidence: 99%